Association between anatomical risk factors and medial meniscus posterior root tears: a retrospective study - Nie Si; Li Hongbo; Gao Jingping; Huang Jiayu; Lan Min (BMC Musculoskeletal Disorders)
Abstract Background The purpose of this study was (a) to investigate the association between the potential anatomical risk factors and medial meniscus posterior root tears (MMPRTs), and (b) to determine the optimal cutoff values of risk factors for discriminating MMPRTs. Methods A retrospective study was conducted, from January 2018 to January 2020, 86 patients with MMPRTs identified by an experienced musculoskeletal radiologist using 3-T magnetic resonance imaging (MRI), and also confirmed during arthroscopic surgery were included in this study. Moreover, MMPRTs patients were matched with 128 patients with other types of medial meniscal tear knees at the same period according to patients’ demographics. We categorized the two patient groups into subgroups based on the causes of meniscus root tears. A subgroup analysis was performed to evaluate the parameter differences between traumatic and degenerative MMPRT in these groups. The associations between clinical and anatomic factors and MMPRTs were analyzed. Additionally, a logistic regression analysis was performed to detect risk factors correlated with MMPRTs. Results Based on the analysis, binary logistic regression models analysis indicated that medial posterior tibial slope (MTS) (odds ratio (OR) = 1.212, P = 0.005), hip knee ankle (HKA) (OR = 1.657, P < 0.001) and medial femoral condyle length/medial tibial plateau length (MFCL/MTPL) (OR = 16.597, P = 0.019) were the risk factors correlated with MMPRTs. A subgroup analysis revealed that the MTS, HKA, and MFCL/MTPL were risk factors associated with traumatic MMPRTs. Additionally, age, MTS, HKA, and MFCL/MTPL were identified as risk factors linked to degenerative MMPRTs. Additionally, the receiver operating characteristic (ROC) curves demonstrated these factors had comparable accuracy at predicting MMPRTs (under the curve were 0.635, 0.700 and 0.627, respectively). The cutoff values of those factors were 7.4º, 2.4º, and 1.2, respectively. Conclusions Based on results from the current study, we identified MTS > 7.4º, HKA > 2.4º and MFCL/MTPL > 1.2 were the risk factors correlated with MMPRTs.